EFFECT OF LIQUIDITY, LEVERAGE AND FIRM SIZE ON GOING-CONCERN AUDIT OPINION WITH PROFITABILITY AS MODERATING VARIABLES IN MANUFACTURING COMPANIES LISTED ON IDX PERIOD 2009-2018 - Ginting, Milawati (International Journal of Public Budgeting, Accounting and Finance, 2020)
The purpose of this study is to examine factors which affecting going concern audit opinion acceptance namely liquidity, leverage and firm size with profitability as a moderating variable. This research uses secondary data with a sample of 30 manufacturing companies listed on the Stock Exchange Indonesia used a purposive sampling method in the 2009-2018 time period. Data analysis techniques in this study used logistic regression analysis and test interaction for moderating variables using Stata 14. Result of this research shows liquidity partially has a significant negative effect on acceptance of going-concern audit opinion , and leverage have an effect significant positive on acceptance of going-concern audit opinion while firm size has no significant negative effect on going audit opinion concern. Interaction test results show that the profitability variable is not able to moderate the effect of liquidity and leverage on the acceptance of going audit opinion concern, but proved to be able to significantly moderate the effect of firm size on going concern audit opinion acceptance.